Karapatrāla dumāram, teraveneka bhāgōaṃ - Anantam, 1919- ('Buk Lavars Pablikēṣans' pracurana, 1977)
On the pamphlet as a genre in Telugu; includes the text of fifteen pamphlets brought out during the period 1929 and 1975.